Math, asked by chotusushma32, 10 months ago

if a = -b then find the value of (a-b)²​

Answers

Answered by merinmathew232
2

Answer:   2b^{2}

Step-by-step explanation:

Given a = -b

(a-b)²​= a^{2} -2ab +b^{2}

        = -b^{2} - 2 × -b × b + b^{2}

        = -b^{2} +2b^{2} +b^{2}

        = 3b^{2} - b^{2}

        = 2b^{2}

Thank U : )

Answered by AnnaEmi
1

Answer:    = 2b^{2}  

Step-by-step explanation:

(a-b)²​=(-b-b)^{2} = -b^{2} - (2 × -b × b) + b^{2}

                         = -b^{2} - (-2b^{2} )  + b^{2}

                         =   - (-2b^{2} )

                         = 2b^{2}  

Similar questions